(3HMSGHGJ eGdjIs - (3eNJGQ(B, (3YdGdjs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2021)
(3GdfabGJ GdYGeI hJbSjeGJgG eY BKGQgG GdGbJUGOjI, h JQTjO GdGfaGb GdYGe heJWdHGJ fLGMg hab BdjGJ GdJSjjQ eY YfGUQ heJWdHGJ fLGMg hBdjGJ GdMce GdQGTO, hCge GdNOeGJ GdLGeYjI hgjcdgG ef OQGSI hJMdjd GdfXGe GdeWHb MGdjG aj bWGYgG hGdejRGfjGJ GdeVNeI, cPdc eQGMd GdUabI GdYehejI ddNOeGJ GdLGeYjI(B.s
(3eQGLY (B127- 128s
Keywords: (3GdNOeGJ GdLGeYjIs; (3GdbWGY GdNGUs; (3GdfabGJ GdYGeIs